Early Nutrition Programming and Health Outcomes in Later Life - Koletzko, Berthold (Springer, 2017)
Obesity has reached epidemic proportions globally and presents a major challenge to policy makers and clinicians alike. Recent research has suggested that obesity has its origins in early life and that early diet can programme a developing fetus’ and young infant’s future susceptibility to obesity. This volume contains recent findings presented at the International Conference on Early Nutrition Programming and Health Outcomes in Later Life: Obesity and Beyond - a satellite meeting of the 15th European Congress on Obesity, held in Budapest in April 2007. Basic scientific research, data from epidemiological studies and clinical trial results were all presented during the programme. This volume includes articles discussing the evidence for an effect of early nutrition programming on later obesity and cardiovascular risk; the growing evidence for an intergenerational cycle of obesity; the role of maternal leptin in programming appetite; possible cellular mechanisms for altered energy balance, including mitochondrial programming and the effects of regulators of metabolism; and how epigenetic changes might be the fundamental underlying mechanism explaining programming effects. Consumer understanding of the concept of early nutrition programming and the extent to which early nutrition programming is taken into account in infant feeding policies are also discussed.